GENERATION Z AND SOCIAL MEDIA: COLLABORATING TO ENHANCE COMPETENCIES - Yustika, Siska; Jaya, Hendra (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Generation Z, as digital natives, possesses a strong attachment to social media, which serves not only as a space for communication and entertainment but also as a medium for developing competencies. This article explores the collaboration between Generation Z and social media in efforts to enhance their skills in the digital era. Using a qualitative approach through in-depth interviews and literature analysis, this study finds that social media plays a crucial role in building competencies such as digital literacy, visual communication, creative marketing, and entrepreneurship. Platforms such as LinkedIn, TikTok, and Instagram have become key channels for self-directed learning, professional networking, and global collaboration. However, this article also identifies significant challenges, including the risk of distraction, consumption of irrelevant content, and the lack of guidance in using social media productively. Based on expert interviews, the study reveals the need for a strategic approach that involves digital literacy education and active supervision from educational institutions and families to optimize the potential of social media. This research contributes to the literature on technology and education by highlighting how Generation Z can effectively utilize social media for personal development and future professionalism.